National Microbiological Laboratory Reporting Service - Bulletin 11. 20 May to 2 June 1977 - whole issue - No author listed, (Communicable Diseases Intelligence, 1977)
Whole-issue pdf, comprising: Discussion on the aims of this Bulletin service "In the last Bulletin we promised a report on the discussions on the service held during the Australian Society for Microbiological meeting in Melbourne in May..." [continues] Article Typhoid outbreak in Melbourne (concluded?) [update from Bulletin 10] Non A, non B hepatitis. [Melbourne, Vic.] Hepatitis B in Vietnamese refugees. [update on previous notifications] Mycoplasma and psitacosis antibodies. [Melbourne, Vic.] National Microbiological Laboratory Reporting Service - Period 11 20 May - 2 June 1977